Mechanism of repetition in transcortical sensory aphasia. Issue 2 (February 1986) - Bando, M; Ugawa, Y; Sugishita, M
Abstract : A typical case of transcortical sensory aphasia (TSA) is presented, in which the Wada test suggests that it is the right hemisphere which enables the patient to repeat orally. It is supposed that one of the mechanisms of preserved repetition in TSA is linked to an exceptional ability for repetition of the right hemisphere, which may help to explain why cases of TSA are so rare.